Study of Optimum Structure of Basal Track Data Applied on LKJ Train Running Monitor Device - 王志伟; 王梅 (机车电传动)
The principle and realization method of optimizing, uniform editing, administering and application of the basal track data used on LKJ train running monitor device in the ambit of the whole railway was introduced. The result of testing on ground as well as on board showed the application was credible and efficient, which met the uniform and flexible application requirements at practice occasion.